Digitalisasi Manajemen Keuangan dalam mengoptimalkan Sistem Pelaporan dan Pengawasan di Lembaga Pendidikan - Holifah Saipur; Saipur Rahman (Prodi Sastra Jepang Universitas Ngudi Waluyo, 2025)
This study aims to analyze how digitalization of governance, particularly through the implementation of e-financial reporting, digital audit trails, and cloud-based data security and reliability systems, contributes to increased transparency, accountability, and data protection in educational institutions. Using a qualitative approach with in-depth interviews and thematic analysis, this study reveals that digitalization can create a more objective, standardized, and difficult-to-manipulate control mechanism. The e-financial reporting system strengthens transparency through open processes and reduces opportunities for irregularities. Digital audit trails provide authentic evidence that facilitates the process of verification, monitoring, and tracking every administrative activity in real time. Meanwhile, data security supported by layered encryption, automatic backups, and emergency recovery access increases internal and external trust in the integrity of information systems. These findings indicate that digitalization not only provides technical tools but also forms a more disciplined, adaptive, and public accountability-oriented governance structure. This study broadens understanding of the relationship between digital technology and organizational culture and provides a theoretical foundation for developing a more reliable and sustainable information system-based educational governance model.